In silico analysis of A novel pathogenic variant in an Iranian Mucopolysaccharidosis IIIB patient identified by targeted next-generation sequencing - Khorrami, Mehdi; Mahdavi, Manijeh; Fakhr, Fatemeh; Kheirollahi, Majid (Iranian Journal of Child Neurology, 2019)
Mucopolysaccharidosis IIIB (MPS IIIB) (Sanfilippo Syndrome Type B; OMIM 252920) is an autosomal recessive metabolic disorder caused by mutations in the NAGLU gene which encode for lysosomal enzyme N-acetyl-glucosaminidase, involved in degradation of complex polysaccharide, heparan sulfate. The disease characterized by progressive cognitive decline and behavioral difficulties and motor function retardation. In this study, using targeted exome sequencing, we identiﬁed a novel heterozygote deletion variant (c.1294-1304 del CTCTTCCCCAA, p.432LeufsX25) in the NAGLU gene in consanguineous parent of a child who was dying in her 14 years old where the diagnosis of death was Mucopolysaccharidosis. Sanger sequencing was used to confirm the candidate pathogenic variants in extended family members and segregation analysis. Computational docking using the Molegro Virtual Docker (MVD) 6.0.1 software confirmed different affinity binding of truncated protein for its ligand-Acetyl-D-Glucosamine. Moreover, with I-TASSER software functional alterations between wild and mutant proteins evaluated. The variant was classified as pathogenic based on the American College of Medical Genetics and Genomics guideline. This study expands the spectrum of NAGLU pathogenic variants and confirms the utility of targeted NGS sequencing in genetic diagnosis and also the utility and power of additional family information.